Analysis of Mathematics Anxiety Experienced by Students of Vocational School in Padang City and The Factors That Affect Them - Yufa Ficanysha Yufa; Netrawati; Neviyarni; Nurfarhanah (Universitas PGRI Yogyakarta, 2023)
Mathematics is a subject that many students fear. This fear has a negative impact, one of which is math anxiety. This study aims to describe the level of math anxiety of SMKN students in Padang and the factors that influence it. This research is a descriptive study with a total sample of 72 students at one of the State Vocational Schools in Padang City. Sampling used a purposive sampling technique, which is based on the results of recommendations, observations, and interviews from counseling teachers and Mathematics teachers at SMKN Padang. This study measures math anxiety which includes math test anxiety, numerical anxiety, and abstraction anxiety. The data collection tool used in this study was a questionnaire with a Likert scale model totaling 38 statement items with 5 alternative answers. Overall, Students' math anxiety is in the high category of 45.83%, which means that many students experience math anxiety, the average student anxiety towards mathematics is the high category which is influenced by personality, environmental and intellectual factors. Keywords:anxiety, math anxiety, vocational school students in the city of padang